PENINGKATAN PERILAKU PROSOSIAL ANAK USIA 5-6 TAHUN MELALUI PERMAINAN LARI ESTAFET - Aprilia, Andini; miranda, Dian; perdina, Siska (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to improve the prosocial behavior of children aged 5"“6 years through relay running games. Specifically, this research aims to identify: (1) learning planning, (2) learning implementation, and (3) the improvement of prosocial behavior, which includes helping, cooperating, and sharing. This research was motivated by the low level of prosocial behavior among children in their daily activities, such as helping each other, cooperating, and sharing. The study employed a Classroom Action Research (CAR) method conducted in two cycles, consisting of the stages of planning, implementation, observation, and reflection. The general objective of this study is to obtain data and information regarding the improvement of children"™s prosocial behavior through relay running games. The results of the study show that the quality of learning planning increased from an average score of 3.3 in Cycle I to 3.8 in Cycle II. Likewise, learning implementation improved from a score of 3.46 to 3.84. In terms of prosocial aspects, there was a significant improvement. In the aspect of helping each other, the number of children who reached the Developing as Expected (BSH) category increased from 0 children (0.0%) in Cycle I to 11 children (61.1%) in Cycle II. In the aspect of cooperation, children in the BSH category increased to 14 children (77.7%). Similarly, in the aspect of sharing, 14 children (77.7%) reached the BSH category.